Potential benefits of pet-facilitated therapy (PFT) in people with disabilities - Zaw, Cho Cho; Ahmad, Norfadzilah; ., Myat Min @ Mohd Omar (SAS publisher, 2019)
The term disability referred to the impairments, activity limitations and restrictions in participation. People with disabilities need special care with alternative therapy to improve their optimum function, quality of life and reduce burdens of their families and communities. Pet facilitated therapy (PFT) has becomes popular among researchers and health care professionals from the developed countries and it is considered as an alternative therapy for people with disabilities. However, the awareness and usage of PFT in Malaysia and Asian countries are still very limited. The lack of information about PFT can lead to the lesser opportunities in searching for physical and mental improvements of the children, elderly and people with disabilities. Thus, this study aims to explore the literature work regarding the potential benefits of PFT in the disabilities in order to highlight the awareness about it among health care providers and public. The systematic literature search was used as a methodology, and three themes namely PFT in clients with physical and mental disabilities, PFT in children with autism, PFT in the elderly with disabilities are presented and discussed. The findings revealed the potential benefits and the use of PFT as an alternative and complementary therapy in people with disabilities after carefully removing the potential risk factors of PFT.